(untitled) - Handy, R. L. (New York, 2007)
Geotechnical Engineering: Principles and Practices offers students and practicing engineers a concise, easy-to-understand approach to the principles and methods of soil and geotechnical engineering. This updated classic builds from basic principles of soil mechanics and applies them to new topics, including mechanically stabilized earth (MSE), and intermediate foundations
Keywords: Foundations,Nền móng; Design and construction,Thiết kế và xây dựng